Political resistance in the saltpetre works of Chacabuco (1973-1975), Antofagasta region, Chile (2019)
This article is about the political resistance, regarding the concentration camps established by the Chilean civil-military dictatorship (1973-1990). With respect to this, the notions of political resistance and concentration camps are observed from an interdisciplinary perspective, according to the complexities and debates understood in a historical and political context as well as in the spatial framework in which they took place, in this case, the saltpetre works of Chacabuco (1924 – 1938), which is currently a heritage site, the operational functioning of which was between November 1973 and April 1975. This background allows us to formulate a main hypothesis that political resistance includes survival strategies that not only maintain a person’s dignity and human rights, but also forms of social reorganization and retaliations that contemplate political, social and cultural actions. The methodology used was that of semi-structured interviews and the testimonial material of survivors, which had previously been published. The secondary sources are of an academic nature and from the press. The narrations of those who currently call themselves Chacabucanos is of special interest. These are people who had been detained, who are originally from Concepción, and were taken from the Regional Stadium to Chacabuco, as they had a previous political link which defined resistance strategies, which are still in existence today.